Dread in Academia – how COVID-19 affects science and scientists - Kowal, Marta; Sorokowski, Piotr; Sorokowska, Agnieszka; Lebuda, Izabela; Groyecka-Bernard, Agata; Białek, Michał; Kowalska, Kaja; Wojtycka, Lidia; Olszewska, Alicja M.; Karwowski, Maciej (Anthropological Review, 2020)
In order to gain an insight into scholars’ concerns emerging from the COVID-19 crisis, we asked scientists from all over the world about their attitudes and predictions regarding the repercussions of this current crisis on academia. Our data showed that the academic world was placed in an unprecedented situation. Results further showed that everybody worked on-line, conducting studies was impossible or highly impeded, and lab work was difficult. Almost a quarter of all scientists participating in our survey were anxious about their scientific employment, and over 25% expected serious financial losses as a consequence of the pandemic. Moreover, we identified sex differences regarding the severity of the COVID-19 impact in the majority of questions. We inferred from this that women perceived to be in a worse situation than men.